Agricultural Pesticide Licensing: Frequently Asked Questions - Sprague, Danielle; Bultemeier, Brett (EDIS, 2022)
Overview of the most frequently asked questions regarding pesticide licensing in Florida. CEU Central article for Citrus Industry Magazine.